2006
DOI: 10.1051/0004-6361:20065625
|View full text |Cite
|
Sign up to set email alerts
|

Velocities and divergences as a function of supergranule size

Abstract: Context. The origin of supergranulation is not understood yet and many scenarios, which range from large-scale deep convection to large-scale instabilities of surface granular flows, are possible. Aims. We characterize the velocities and divergences in supergranulation cells as a function of their size. Methods. Using local correlation tracking, we determine the horizontal flow fields from MDI intensity maps and derive the divergences. The smoothed divergences are used to determine the cells for various spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 18 publications
7
35
1
Order By: Relevance
“…We identified seven NCs using this method; they are shown on a single frame in Figure 2. As expected, the identified NCs were separated by distances of 15-30 Mm, which is approximately the range of supergranule diameters (Meunier et al 2007). …”
Section: Feature and Network Concentration Trackingsupporting
confidence: 73%
“…We identified seven NCs using this method; they are shown on a single frame in Figure 2. As expected, the identified NCs were separated by distances of 15-30 Mm, which is approximately the range of supergranule diameters (Meunier et al 2007). …”
Section: Feature and Network Concentration Trackingsupporting
confidence: 73%
“…The amplitude of the difference agrees with the result of the previous section, within the errorbars. We have not observed any significant variations in these residuals with the amplitude of the maximum divergence (which is correlated with the size of the cell, Meunier et al 2007c) nor with the maximum correlation.…”
Section: Horizontal Divergence Feature Trackingmentioning
confidence: 58%
“…We therefore chose to track supergranules using horizontal divergence maps as determined by Meunier et al (2007a,b,c). We used the same data sets as in Meunier et al (2007a,b) while Meunier et al (2007c) used only a subset. Tracking magnetograms is used for reference, and Doppler features are tracked for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Even more recently, Hathaway et al (2006) argued that the supergranulation pattern superrotation inferred from Doppler shifts was due to projection effects on the line-of-sight signal. Using correlation tracking of divergence maps derived from intensity maps (Meunier et al, 2007c) and comparing it with direct Doppler tracking, Meunier and Roudier (2007) confirmed the existence of projection effects with the latter method, but found that the supergranulation pattern inferred from divergence maps was still superrotating, albeit at smaller angular velocities than those inferred by Duvall Jr (1980) and Snodgrass and Ulrich (1990). For a detailed discussion on the identification of supergranulation rotational properties with helioseismology, we refer the reader to the review article by Gizon and Birch (2005) on local helioseismology.…”
Section: Rotational Properties Of Supergranulesmentioning
confidence: 80%
“…From these data, they derived a rather small "diameter" in the 12 -20 Mm range. Using a similar technique, Meunier et al (2007c) found a mean value for Living Reviews in Solar Physics http://www.livingreviews.org/lrsp-2010-2 supergranule diameters around 30 Mm. As underlined in these papers, the size of supergranules very much depends on the smoothing procedure used in the data processing.…”
Section: Length Scalesmentioning
confidence: 99%